Femur 3D-DXA Assessment in Female Football Players, Swimmers, and Sedentary Controls - Amani, Amineh; Bellver, Montse; del Rio, Luis; Torrella, Joan Ramon; Lizarraga, Antonia; Humbert, Ludovic; Drobnic, Franchek (International Journal of Sports Medicine, 2023)
Cortical and trabecular volumetric bone mineral density (vBMD), cortical thickness and surface BMD (sBMD, density-to-thickness ratio) were analyzed in the proximal femur of elite female football players and artistic swimmers using three-dimensional dual-energy X-ray absorptiometry (3D-DXA) software and compared to sedentary controls. Football players had significantly higher (p<0.05) vBMD (mg/cm3) in the trabecular (263±44) and cortical femur (886±69) than artistic swimmers (224±43 and 844±89) and sedentary controls (215±51 and 841±85). Football players had also higher (p<0.05) cortical thickness (2.12±0.19 mm) and sBMD (188±22 mg/cm2) compared to artistic swimmers (1.85±0.15 and 156±21) and sedentary controls (1.87±0.16 and 158±23). Artistic swimmers did not show significant differences in any parameter analyzed for 3D-DXA when compared to sedentary controls. The 3D-DXA modeling revealed statistical differences in cortical thickness and vBMD between female athletes engaged in weight-bearing (football) and non-weight bearing (swimming) sports and did not show differences between the non-weight bearing sport and the sedentary controls. 3D-DXA modeling could provide insight into bone remodeling in the sports field, allowing evaluation of femoral trabecular and cortical strength from standard DXA scans.
Keywords: 3D analysis; bone health; exercise